1999
DOI: 10.1177/0970846419990308
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Financial Assistance for Technological Modernisation of Small Industries: Opportunities and Constraints

Abstract: Small-scale industries play an important role in the economic development of a developing country. like India. Having the inherent. advantages of low investment and high potential for employment generation, diversificaiton of industrial base, dispersal of industries in rural and semi-urban areas and equitable distribution of national income, small industries have been accorded a strategic place in India's planned economic development.The small industrial sector in India has been making significant progress sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study concluded that SFCs are equally important as all India DFIs (Developmental Financial Institutions) and commercial banks for national development and therefore, should be treated on par. Chadha (1999) indicated that the growth in hire-purchase of machinery supplied by NSIC (National Small Industry Corporation) has increased from 9.16 crore in 1972-73, to Rs. 17.58 crore in 1988-89, showing an average annual growth of 9.48%.…”
Section: VImentioning
confidence: 99%
“…The study concluded that SFCs are equally important as all India DFIs (Developmental Financial Institutions) and commercial banks for national development and therefore, should be treated on par. Chadha (1999) indicated that the growth in hire-purchase of machinery supplied by NSIC (National Small Industry Corporation) has increased from 9.16 crore in 1972-73, to Rs. 17.58 crore in 1988-89, showing an average annual growth of 9.48%.…”
Section: VImentioning
confidence: 99%